2021
DOI: 10.4269/ajtmh.21-0380
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Anxiety Disorder and Depressive Symptoms among Pakistani Population during the Second Wave of the COVID-19 Pandemic: A Regression Analysis

Abstract: Over a span of 1 year, with millions infected, COVID-19 has spread to every part of the world and now poses a health threat to each and every one of us. The outbreak has consequently resulted in multiple health problems such as stress, anxiety, depressive symptoms, insomnia, panic, and denial globally. Several factors have contributed to this rising number of psychiatric consults all over the world. The primary objective of this study was to investigate the impact of COVID-19 pandemic on the mental health of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
(48 reference statements)
0
13
0
3
Order By: Relevance
“…The depression (p-value = 0.021) and anxiety (0.012) symptoms were significantly associated with COVID suspect (with ROM), COVID (with ROM), and only ROM. Previous studies also report a higher association between depression and anxiety symptoms during the COVID-19 pandemic [6][7]. A previous study by Ahuja et al [22] reported that 76.4% of patients were experiencing anxiety or sadness before surgical intervention.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The depression (p-value = 0.021) and anxiety (0.012) symptoms were significantly associated with COVID suspect (with ROM), COVID (with ROM), and only ROM. Previous studies also report a higher association between depression and anxiety symptoms during the COVID-19 pandemic [6][7]. A previous study by Ahuja et al [22] reported that 76.4% of patients were experiencing anxiety or sadness before surgical intervention.…”
Section: Discussionmentioning
confidence: 96%
“…Previous evidence, literature, and media highlighted the need for assessment of suicidal risk, as the pandemic overall had set in a gloomy picture [5][6][7][8][9]. The finding of 98% cases of low suicide risk could be explained by the regular counseling services which were provided for all the patients after initial evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 2 years, COVID-19 has spread around the world and infected millions of people. [ 43 ] The pandemic has changed our way of life and threatened our health. In addition to causing physical health problems globally, the outbreak has also made a major impact on our mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety levels have increased with the entrance of the fourth wave of the COVID-19 pandemic in Pakistan, and with the predominance of the Delta variant, anxiety levels have increased [ 4 ]. In the second wave, a regression analysis evaluating Generalized Anxiety Disorder and depressive symptoms in 500 participants found that 25.4% had GAD and 18.8% had depressive symptoms indicating severe psychological impacts of the pandemic [ 5 ]. As of August 2021, 1,160,119 confirmed COVID-19 cases and 25,788 deaths had been reported, with a positivity rate of 6.78% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%